(untitled) (PerCursos, 2010)
Neste artigo, será analisada a problemática do relativismo cultural apresentada por Peter Burke, questionando este conceito quando tratamos da imposição de valores culturais de uma adulto sobre uma criança, em detrimento de sua integridade física, em uma prática culturalmente aceita no norte da África, a retirada do clitóris, ou clitoridectomia. Serão analisadas também formas de enfrentamento do problema do combate a tal prática pelos organismos de direitos humanos internacionais, mesmo que tal enfrentamento seja rotulado como uma intervenção na cultura de uma determinada população. Palavras-Chave: Relativismo cultural. Absolutimo Cultural. Clitoridectomia. Direitos humanos. Feminismo. Abstract In this article, will be analyze the problematic of the cultural relativism presented by Peter Burke, questioning this concept when we deal with the imposition of cultural values of an adult on a child, in detriment of its physical integrity, one practical culturally accepted on the north of Africa, the withdrawal of the clitoris, or Clitoridectomia. Will be also analyze forms of confrontation of the problem of the combat to such practical for the organisms of international human rights, even that such confrontation is friction as an intervention in the culture of a determined population. Keywords: Cultural relativism. Cultural absolutism. Clitoridectomia. Human rights. Feminism.